Effects of protein concentrate supplementation-based diet on growth and nutritional status in dairy heifers: Protein concentrate supplementation in heifer diet - Islam, Md. Shakil; Habib, Md. Rezwanul; Islam, Mohammad Ashiqul; Rashid, Md. Harun -ur- (Journal of the Bangladesh Agricultural University, 2019)
This experiment was conducted to study the effect of protein rich ingredients supplementation into concentrate diet on body growth and some biochemical blood parameters of crossbred heifers. Six heifers aged above two years were divided into two equal groups: (a) control (farm feeding practices) and (b) protein supplemented. Soybean meal and mustard oil cake were added in concentrate mixture as protein supplement in supplementary group. The heifers of both dietary groups had access to required amount of para and german grass as basal roughage. Growth measurement parameters were studied at fortnightly; blood collection and its analysis for various blood metabolites were assayed at thirty days intervals. It was noticed that heifer dry matter intake was significantly (P=0.001) affected by the diet and found higher in supplemented group than control group. About 16% higher (P=0.149) body weight gain was found in supplemented group compared to control group. Protein supplemented heifer showed 0.12, 0.74 and 0.26 cm higher gains for wither height (P=0.01), body length (P=0.002) and heart girth (P=0.016), respectively. The blood biochemical profile revealed that serum urea and blood urea nitrogen concentrations were higher (P=0.015) in protein supplemented group compared to that of the control group. In conclusion, supplementation of protein rich ingredients in heifer diets might increase the growth measurements and blood serum protein status which would be more advantageous for the development of dairy herd replacement stock J. Bangladesh Agril. Univ. 17(1): 45–49, March 2019